New thiophene-based poly(azomethine)s bearing tetraphenylsilane moieties along their backbone. Optical, electronic, thermal properties and theoretical calculations. (5th May 2020) - Sobarzo, Patricio A.; Jessop, Ignacio A.; Mariman, Andrea P.; González, Alexis F.; Saldías, Cesar; Schott, Eduardo; Zarate, Ximena; Hauyon, René A.; Recabarren-Gajardo, Gonzalo; González-Henríquez, Carmen M.; Tundidor-Camba, Alain; Terraza, Claudio A.
Graphical abstract: The synthesis and characterization of processable poly(azomethine)s with tetraphenylsilane cores and thiophene/bitiophene units along their backbone (PAZThAs) is reported for the first time. The new materials are soluble in a variety of organic solvents and thermally stable. Their HOMO, LUMO, and bandgap values were fine-tunned by changing the specific structure of the repetitive unit and their magnitudes were confronted with DFT theoretical calculations. Due to their optical and electronic properties, PAZThAs could emerge as a promising alternative as donor material for optoelectronic applications. Highlights: New thiophene-based poly(azomethine)s bearing tetraphenylsilane moieties. Optical, electronic, thermal properties and theoretical calculations. Band gap value closely similar to polythiophene derivates studied in PSCs. TPS-cores interrupt of π-conjugation and allow to control the HOMO and LUMO energy levels. Abstract: A new series of conjugated thiophene-based poly(azomethine)s (PAZThAs) containing tetraphenylsilane (TPS) cores and thiophene or bithiophene moieties along the backbone were obtained from silicon-containing diamines and commercial 2, 5-thiophenedicarboxaldehyde and 2, 2′-bithiophene-5, 5′-dicarboxaldehyde through high-temperature polycondensation reactions. Solution-processable polymers were obtained in high yields (74–96%), high average molecular weight (Mw: 2, 900–22, 200 g/mol), with adequate polydispersity (closed to 2), and high thermal stability (T10% : 326–488 °C). The thiophene-based PAZ showed suitable absorptions and emissions in the UV–vis range with moderate Stokes shifts (46 to 65 nm). The lower band gap value was observed for PAZ2ThA2 (1.98 eV) that is closely similar to polythiophene derivates studied in polymer solar cells (PSCs). The calculated HOMO energies values are in the range of −5.82 eV to −5.42 eV, while the LUMO energies ranging from −3.56 to −3.39 eV. Compared to fully π-conjugated PThs, the PAZThAs tend to possess higher LUMO energies and similar HOMO energies, which is attributable to the electronic influence of the TPS-cores. This study motivates future researches on TPS building-blocks based PAZs.